The application of dynamic game theory to participant's interaction mechanisms in lean management. (January 2020) - Jing, Shuwei; Li, Rui; Niu, Zhanwen; Yan, Junai
Highlights: Enterprises should engage experts to undertake training activities for employees. Senior managers should aim to improve the motivation of middle managers. The effort level of middle managers and experts is improved by employees' effort. Senior managers should determine the appropriate income distribution coefficient for experts. Senior managers should co-ordinate the relations between each coefficient. Abstract: This research focuses on the problems that enterprises are affected by multiple stakeholders in the process of lean management. Based on the dynamic game theory, through the construction of a three-stage game model, the article has researched on the interaction mechanism between internal and external stakeholders that affects the implementation of enterprise lean management. Through the research, the following conclusions are drawn: (1) At the beginning of lean management, hiring the third-party consultant experts to train employees, which is conducive to improving management efficiency; (2) the effort level of middle managers has nothing to do with the control of senior managers; (3) senior managers should not be too many constraints on third-party consultant experts; (4) senior managers should strive to coordinate the interests of all parties. The purpose of the paper is aimed to provide a reference of theory and practice of the implementation of lean management for enterprises.